Identifikasi Kecelakaan Kerja pada Pekerjaan Kolom Beton Pembangunan Rumah Tinggal 2 Lantai di Perumahan Surabaya. - Feriza Nadiar; Danayanti Azmi Dewi Nusantara; Puguh Novi Prasetyono (Universitas Dr. Soetomo, 2023)
The rate of population growth in the city of Surabaya, which decreased in 2022, does not reduce the number of people's need for property in the form of residential houses with freehold titles. This number of needs has increased and has an impact on the increase of residential construction projects in residential areas. All types of construction projects are not risk-free, each construction has its risks, especially in the Occupational Health and Safety aspect, which is often neglected in residential construction projects compared to high-rise building construction projects. This study aims to identify work accidents in two-story residential construction projects, especially in concrete column work where in research it is often stated that the work has a risk value that tends to be high compared to other activities. This research method uses descriptive qualitative methods by conducting direct field observations, interviews, and also distributing questionnaires. The results of the analysis of this study indicate that the type of work variable in the entire concrete column work that has the highest risk value compared to the others is casting and ironing work. Meanwhile, for the potential risk variable, which totaled 13, there are three potential risks with the highest risk values, namely: fine iron dust entering the eye, falling from a height when casting, and injuring the hand due to hammer blows. From the overall results of the analysis, concrete column work has an average risk value that is included in the medium category. Even though the risk level of column work in this two-story residential project is not as high as in a high-rise building construction project, it should be realized that the risk potential still exists even though it is classified as in the medium category so the Occupational Health and Safety aspect needs to be considered again.